IDENTIFIKASI DAMPAK PERKEMBANGAN TEKNOLOGI TERHADAP TENAGA KERJA TOKO RITEL INDONESIA: STUDI KASUS TOKO X - Luciana Saragih (Jurnal Kependudukan Indonesia, 2019)
Technological developments in the era of the fourth industrial revolution are like two sides of a coin. On one hand, they open up opportunities to achieve progress and prosperity; On the other hand, machines and automation replace the role of workers with low skills. The author studied Store X, the first future store prototype in Southeast Asia using qualitative methods, which included observation, in-depth interviews, and SWOT analysis techniques. The results of the study are that X stores use a variety of cutting-edge technologies such as artificial intelligence, big data, cloud computing, and connected digital equipment systems. The technology is beneficial for retail and consumer entrepreneurs, but whether or not to benefit workers is still a question, because the effect will be seen when the implementation of this technology extends in the next few years. Low-skilled retail workers must get training from the company, and the most important thing is to have a strong willingness to increase his capacity to remain relevant to the needs of the retail industry in the future. Only workers who master STEM (science, technology, engineering and math) well will be able to fill this new job market. Therefore, all stakeholders need to collaborate to raise the level of education and skills of these workers.